Tomada de depoimento na Justiça brasileira : a dêixis e os pontos de referência pessoal, espacial e temporal na narrativa - Colares, Virgínia (Language and Law / Linguagem e Direito, 2017)
This paper investigates how the inclusion of a narrative when giving evidence in a court of law can contribute to the successful identifcation of contradictions. It describes the discursive structure of the communicative event of statement taking in Brazilian courts, in particular the use of deixis and personal, spatial and temporal reference points in the narrative. The methodology used is derived from the Ethnography of Speech. This article presents a structural analysis of Labov’s (1972) narrative model in order to contribute to the typology of the communicative event. The opening question – how does a narrative statementtaking provide more opportunities to capture contradictions? – guides the corpus analysis of these fragments throughout the article.